Thermal comfort and energy consumption in a UK educational building - Barbhuiya, S.; Barbhuiya, Salim (ELSEVIER, 2013)
Educational buildings are responsible for a large amount of UK’s non-industrial energy consumption. Hence, it is important not to overlook their energy performance. The primary aim of this study was to investigate how the ventilation strategy of a typical educational building in the UK will affect the energy consumption and to what extent this will impact the thermal comfort of the occupants. The building investigated is Loughborough University’s Civil & Building Engineering building. Data from monitoring indoor temperature and lighting levels are used to discuss the trends in thermal and visual comfort respectively. The simulations results from IES are used to compare the reduction in the energy consumption. It was found that the Ground Floor offices had the problem of indoor temperatures remaining below the lower limit of 19 C. The average working plane illuminance in winter was below the CIBSE limit of 300 lux for office spaces. The thermal comfort was not adequately achieved during the occupied hours during winter in the three Second Floor offices. Therefore, it is recommended that strategies like better integration of the entrance of the building with the interior spaces and adopting dimming profile for lighting control can help in reducing the energy consumption significantly.